(untitled) (Journal of International Crisis and Risk Communication Research, 2023)
This study explored perceptions and effects of the Wireless Emergency Alert (WEA) system for COVID-19 public health messaging after a message was sent to Pennsylvania residents in November 2020. Survey and interview research were conducted to understand the targeted publics’ reactions to this message and factors impacting potential behavior change. Findings showed residents who received the WEA expressed greater feelings of anger and surprise about the COVID-19 threat compared to those who did not. Additionally, for participants who did not receive the WEA message, higher arousals of fear and perceptions of threat severity predicted a higher likelihood that they would have changed their Thanksgiving plans. Interview data suggested positive emotions toward using WEAs for public health crises in general.